2020
DOI: 10.3390/safety6020020
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a LED Lighting Crosswalk on Pedestrian Safety: Some Experimental Results

Abstract: The research presented in this paper is focused on the definition of a new methodology for evaluating how illuminated crosswalks influence drivers’ behavior when approaching the zebra in nighttime conditions. The proposed methodology is based on in situ speed measurements, and cars’ speed was detected in an urban road segment of the city of Rome with a Telelaser instrument. Vehicles speed profiles are measured in the same road segment both in LED-illuminated conditions and in non-illuminated conditions. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…They performed field tests using a passenger car and, based on an analysis of object detection distances, showed that 20 lx with metal-halide lamps and 30 lx with high-pressure sodium lamps provided sufficient illuminance levels for spotting objects. The effect of spectral distribution on pedestrian visibility was also studied by Pena-Garcia et al [9], Markvica et al [10], Davidovic et al [11], and Pastella et al [12]. Based on their research, the authors found a positive effect of LED lamps on pedestrian visibility.…”
Section: Lighting Requirements At Pedestrian Crossingsmentioning
confidence: 86%
“…They performed field tests using a passenger car and, based on an analysis of object detection distances, showed that 20 lx with metal-halide lamps and 30 lx with high-pressure sodium lamps provided sufficient illuminance levels for spotting objects. The effect of spectral distribution on pedestrian visibility was also studied by Pena-Garcia et al [9], Markvica et al [10], Davidovic et al [11], and Pastella et al [12]. Based on their research, the authors found a positive effect of LED lamps on pedestrian visibility.…”
Section: Lighting Requirements At Pedestrian Crossingsmentioning
confidence: 86%
“…Rapid advancements in the field of LED technology and considerable energy savings as a result of such technology make it more appealing. An experimental study on the influence of illuminated crosswalks on drivers' behavior and pedestrians' safety in Rome [22] showed the promising impact of LED lighting on drivers' behavior and the improved safety of pedestrians. The conversion of HPS lamps to LED lamps in street lighting is investigated in [6], which shows that a useless luminous flux causes electricity loss.…”
Section: Literature Review On Led Lampsmentioning
confidence: 99%
“…The lifetime of the PV system is 25 years except for the battery with a replacement period of seven years and the inverter with a replacement period of 13 years. The LCC is calculated using equation [61] with the salvage value included as, LCC = Initial cost of PV system + installation cost + cost of the replaced batteries + cost of replaced inverter+maintenance and operation cost − salvage value (22) Inverter Rating = 1.2 × 80 × 245 = 23, 520 W…”
Section: Life Cycle Cost Analysismentioning
confidence: 99%
“…Enhancement of pedestrian visibility is crucial for maintaining pedestrian safety during the night. Patella et al (2020) identified that low lighting conditions are a major determinant of pedestrian collisions as well as deaths at night. Increasing the number of lights at the crossing and using fluorescent reflectors at crossing signals would be an effective manner which can lead to increased pedestrian visibility.…”
Section: Enhancement In Pedestrian Visibilitymentioning
confidence: 99%